Analisis Produktivitas Tenaga Kerja Proyek Gedung Apartemen Bandaraya - Tri Santi; Junus Mara; Meti (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
Productivity as a measure of whether a project is implemented effectively and efficiently or not. Lack of awareness of productivity will be the cause of the low work produced resulting in large losses in the implementation of construction projects. To find out labor productivity in steelwork and installation of column formwork in the Airport Apartments project, the purpose of this study is to analyze labor productivity in column ironing and formwork installation in the Airport Apartment development project by comparing productivity in SNI. Data collection was carried out through direct surveys in the field by processing the data obtained. The data analysis method for calculating workforce performance uses a descriptive analysis method by calculating the productivity of each workforce. Based on the findings of the analysis and discussion carried out, it can be concluded from this study that the results of calculating the productivity of column work and comparing it with the reference (SNI 7394-2008) are accurate. It can be seen that the value of field productivity is 185.4333 Kg/Oh for iron work and 57 m²/Oh for formwork work. The productivity value according to SNI is 142.887 Kg/Oh for ironing work and 3.03 m²/Oh for formwork work. Then for comparison with references, there is a significant difference between field productivity and productivity calculated using references.